Parents' experiences of participation in physical activities for children with cerebral palsy – protecting and pushing towards independence. Issue 8 (10th April 2017) - Lauruschkus, Katarina; Nordmark, Eva; Hallström, Inger
Abstract: Purpose : To explore how parents of children with cerebral palsy (CP) experience their child's participation in physical activities and to identify facilitators and barriers for being physically active and reducing sedentary behaviour. Methods : Twenty-five parents of sixteen children, aged 8–11 years old with CP, with varying gross motor, cognitive and communicative functions and with different cultural backgrounds, participated in focus group or individual interviews. Content analysis was used for analysis. Results : Five subcategories addressing children's participation in physical activity were found: "Belonging and taking space in the family", "Important persons facilitating and hindering", "Friends important but hard to get", "Good for the body but challenging" and "Availability and opting out possibilities". The subcategories built the main category "Protecting and pushing towards independence", expressing the challenges parents experienced when their child wanted to be physically active. Conclusions : Parents desire competent persons to be available for support in participation in physical activities. They want support in finding friends for their child to be physically active with. Family culture and attitudes affect their child's motivation for being physically active and should be taken into account when designing interventions for increased participation in physical activities and for reduced sedentary behaviour in children with disabilities. Implications for Rehabilitation: Friends and competent adults facilitate participation in physical activities and reduce sedentary behaviour. Information on accessible and tailored physical activities is an important facilitator for participation in physical activities. Service planning and design of interventions may be facilitated by taking the individual family culture into account.